Venous volume and compliance in the calf and forearm does not change after acute endurance exercise performed at continuous or interval workloads. Issue 11 (7th June 2022) - Iimura, Yasuhiro; Saito, Michiko; Oue, Anna
Abstract: Short‐term endurance exercise training for 6–8 weeks leads to increases in venous volume and compliance in the limbs. However, it is not known whether these venous vascular properties are improved by acute endurance exercise. We examined the effects of acute endurance exercise involving continuous or interval workloads on venous volume and compliance in the exercising (calf) and non‐exercising (forearm) limbs. Sixteen healthy young volunteers performed cycling exercise involving a continuous workload of 60% heart rate (HR) reserve or an interval workload of 40% HRreserve and 80% HRreserve, alternating every 2 min, for a total of 32 min each. Before and 60 min after acute cycling exercise, venous volume in the calf and forearm was measured by venous occlusion plethysmography during a cuff‐deflation protocol with a venous collecting cuff wrapped to the thigh and upper arm and strain gauges attached to the calf and forearm. The cuff pressure was maintained at 60 mmHg for 8 min and was then deflated to 0 mmHg at a rate of 1 mmHg/s. Venous compliance was calculated as the numerical derivative of the cuff pressure–limb venous volume curve. In both the calf and forearm, the cuff pressure–venous volume curve and the cuff pressure–venous compliance relationship did not differ between before and 60 min after exercise involving continuous or interval workloads. These results suggest that acute exercise does not improve venous volume and compliance in both the exercising and non‐exercising limbs. Abstract : This result suggests that acute endurance exercise might not improve venous volume and compliance in both the exercising and non‐exercising limbs.